2017
DOI: 10.1021/acsami.7b00885
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Antibacterial Film Based on Conjugated Polyelectrolyte/Silver Nanocomposites

Abstract: In this work, we report a flexible film based on conjugated polyelectrolyte/silver nanocomposites with efficient antibacterial activity. A flexible poly(dimethylsiloxane) film served as a substrate for deposition of nanostructured silver. A light-activated antibacterial agent, based on the cationic conjugated polyelectrolyte poly({9,9-bis[6'-(N,N-trimethylamino)hexyl]-2,7-fluorenyleneethynylene}-alt-co-1,4-(2,5-dimethoxy)phenylene)dibromide (PFEMO) was self-assembled on the negatively charged substrate. By cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…The polymer films are often susceptible to bacterial fouling, which greatly hinders the utilization of films. [15][16][17][18] Antimicrobial modification of films is highly desirable to reduce the risk of bacterial contamination. A large volume of research work has demonstrated that graphene-based materials present antibacterial property owing to membrane puncture induced by the sharp edges of graphene nanosheets and supported by the oxidative stress mechanism, [19][20][21] among which GO showed the best biocidal efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…The polymer films are often susceptible to bacterial fouling, which greatly hinders the utilization of films. [15][16][17][18] Antimicrobial modification of films is highly desirable to reduce the risk of bacterial contamination. A large volume of research work has demonstrated that graphene-based materials present antibacterial property owing to membrane puncture induced by the sharp edges of graphene nanosheets and supported by the oxidative stress mechanism, [19][20][21] among which GO showed the best biocidal efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Excited fluorescent conjugated polymers can sensitize oxygen to generate ROS for photodynamic anti‐bacteria. We developed a flexible MEF platform based on AgNP and CP PFEMO that showed efficient antibacterial activity, as shown in Figure a and b . The spectra of the SPR overlapped mainly with the absorption of CP PFEMO, indicating an excitation enhancement of the MEF (Figure c).…”
Section: Mef‐based Fluorescent Platformsmentioning
confidence: 99%
“…Enhanced fluorescence (d), phosphorescence (e), ROS generation (f), and bacterial killing efficiency (g) of PFEMO on the MEF platform. Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Mef‐based Fluorescent Platformsmentioning
confidence: 99%
See 2 more Smart Citations